Physical, Mechanical, Thermal and Morphology Properties of Biodegradable Polymer Nanocomposites and Its Comparison - Md Rezaur, Rahman; Lai, Josephine Chang Hui; Sinin, Hamdan (EDP Sciences, 2016)
Polyvinyl alcohol (PVA) and Polylactic acid (PLA) were fabricated with the addition of nanofiller such as nanoclay and fumed silica through suitable technique namely solution intercalation film casting. These nanocomposites undergo Fourier transform infrared spectroscopy, scanning electron microscopy, tensile test and thermogravimetric analysis. FT-IR results showed that both nanocomposites were well intercalated with fumed silica and clay with the reduction of hydroxyl groups. From SEM results, it proved that clay 1.28E is more suitable to be intercalated with PLA matrix while clay 1.30E is more suitable to be introduced into PVA matrix. The addition of both nanofillers improved the tensile properties of the nanocomposites. TGA results showed that polyvinyl alcohol/fumed silica/clay (PVA/fsi/clay) had better thermal stability compared to polylactic acid/fumed silica/clay (PLA/fsi/clay) nanocomposites. Both nanocomposites are applicable in the biomedical field.